THE DIFFERENCES IN SEXUAL FUNCTION BETWEEN WOMEN AFTER CESAREAN SECTION WITH INDICATION OF SECOND STAGE DISTOCIA AND ELECTIVE INDICATION - Nindrea, Ricvan Dana (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
This research want to know the difference between a womans sexual function after childbirth with Caesarean section on indications second stage dystocia and elective.This study is observational analytic with cross sectional design using comparative in M. Djamil General Hospital and Networking Hospital. Obtained samples are 26 women after childbirth cesarean section for second stage dystocia and 26 women after elective Caesarean section were spawned from term pregnancies that meet the inclusion and exclusion criteria. Data analysis was performed using univariate and bivariate using independent T test. The average female sexual function after cesarean section indication of second stage dystocia is 27,70 Â± 8,53 and female sexual function after elective Caesarean section indications are 33,55 Â± 3,18. Statistical test results are known there is a difference in sexual function between women after Caesarean section indication of second stage dystocia and elective p = 0,003 (p â¤ 0,05). There is a difference between a womans sexual function after childbirth Caesarean section on indications second stage dystocia and elective.